If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 + -1x = 266 Solving 86 + -1x = 266 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-86' to each side of the equation. 86 + -86 + -1x = 266 + -86 Combine like terms: 86 + -86 = 0 0 + -1x = 266 + -86 -1x = 266 + -86 Combine like terms: 266 + -86 = 180 -1x = 180 Divide each side by '-1'. x = -180 Simplifying x = -180
| 4(2x-3)+6=18 | | 38=2x-5y | | 5+3u=-1 | | 3(5x-9)=15x-27 | | 5x-7=7x-187 | | 2y+4=-2 | | 13=4m+7-m | | 7n-4+8n-3= | | 4.4q-3.7-5.5q=-0.1q-3.7 | | -19=5v+6 | | 0.08(y-8)+0.14y=0.18y-1 | | -14=-2+3v | | 6(6v+6)-5-6v=1 | | 5(x+6)=3(x+10)+2x | | (4x-4)+(3x+12)=0 | | 4x+x-6=5 | | 58=4x+10 | | -7(v+4)+4v+5=5v+11 | | 2(5r-9)= | | -3c-5-2c+6= | | 21x-11-12x=3(3x+5)+4 | | 1/9=5/3x | | (68-32)5/9 | | 8n-17n=18 | | 9x^2-11x-114=0 | | 8=3y-13 | | 2x-6=8x-14 | | 7x-1-6x=0 | | 7+(6-8p)-9=0 | | 167=82-x | | 194-u=270 | | 5y+16=3y-8 |